THE INFLUENCE OF INFORMATION TECHNOLOGY, INFORMATION SYSTEM, AND INFORMATION MANAGEMENT CAPABILITY ON ORGANIZATIONAL PERFORMANCE OF PT. XYZ - Yoga, Nyoman Alit Suciatiningrum; Firdausy, Carunia Mulya (International Journal of Application on Economics and Business, 2024)
One of the problems faced by the pharmaceutical company in Indonesia is how to improve organizational performance. This research seeks to analyze the influence of information technology, information systems, and information management capability on organizational performance by taking into account a pharmaceutical company PT XYZ. The source of data was obtained from questionnaires. The total number of respondents sampled by non-probability sampling method was 135 respondents as Area Managers spread throughout Indonesia. The method to analyze the data was by employing Partial Least Square-Structural Equation Modeling (PLS-SEM). The results show that information technology, information systems, and information management capability have a positive and significant influence on the organizational performance of PT XYZ. These suggest that PT XYZ needs to give attention on how using an integrated information system which supported by information technology, and equipped with good data or information management capabilities to improve its organizational performance. This can be done by easing access, presenting data that summarizes all information correctly, and correcting the format to assist decision-making as well as management's commitment to continuing to develop information systems to improve the organizational performance of PT. XYZ.